Predicting role of Myc-induced nuclear antigen 53 in determining the development and severity of systemic lupus erythematosus - Zamani, Batool; Dadgostar, Ehsan; Akbari, Hossein; Motedayyen, Hossein; Nikoueinejad, Hassan (Frontiers in Immunology, 2024)
Introduction Systemic lupus erythematosus (SLE) as an autoimmune disease can relate to an imbalance between regulatory T cells (Tregs) and Th17 cells. Previous reports have shown that Myc-induced nuclear antigen (Mina) 53 protein is involved in the developments of Tregs and Th17 cells. Therefore, the current study focused on determining whether Mina53 level is correlated to the severity of SLE. Methods The blood samples were collected from 60 patients with SLE (30 cases with mild SLE and 30 cases with severe SLE) and 30 healthy subjects. The serum concentration of Mina53 was measured using enzyme-linked immunosorbent assay (ELISA). The expression of Mina53 gene was assessed using real-time PCR method after extracting RNA from isolated peripheral blood mononuclear cells and synthesizing cDNA. Results Patients with SLE showed significant increases in the serum level and gene expression of Mina53 compared to healthy subjects (P<0.001). Furthermore, serum level and gene expression of Mina53 showed significant effects on SLE disease and its severity (P<0.01). There was the highest sensitivity and maximum specificity in the cut-off point of Mina53 serum level equal to 125.4 (area under the curve (AUC)=0.951) and Mina53 expression level equal to 8.5 (AUC=0.88) for SLE diagnosis. The cut-off point of Mina53 serum level equal to 139.5 (AUC=0.854) and the cut-off point of Mina53 expression level equal to 8.5 (AUC=0.788) had the highest sensitivity and maximum specificity determining severe forms of SLE. Discussion Our results showed that the changes in serum and expression levels of Mina53 have significant effects on SLE disease and its severity. These levels may be considered as diagnostic and predictive markers for SLE.